Representasi Kepercayaan Diri pada Wanita - Diana Putri Rahmadhani; Alex Sobur (UNISBA Press, 2024)
Abstract - This study is based on the background of many women who are faced with situations and conditions that make them feel worried and anxious about something. This can be triggered because there are demands by the closest person. Therefore, Yura Yunita released a song entitled